Malaysian journalists’ perceptions on the role of the media - Tamam, Ezhar; Abdullah, Ain Nadzimah (Pergamon Press, 2014)
In this study, the authors examined the perception of Malaysian journalists with regard to the role of the media in Malaysian civil society. A total of 182 journalists participated in the study via self-administered survey questionnaires. Results revealed that Malaysian journalists have mixed views on the role of the media in the Malaysian media environment, which is highly regulated by the government. They are highly supportive of the role of the media as “interpreter”, “disseminator”, “analytical-objective”, “mobilizer” compared to the role of media as “watchdog”, in support of the argument that the country's socio-political environment shapes media environment, which in turn influences how journalists conceive their roles. Education and training background and years in journalism have no significant influence on their views concerning the importance of the role of the media. Implications of these findings are discussed in this study.